Hypothalamic agrp and pomc mRNA Responses to Gastrointestinal Fullness and Fasting in Atlantic Salmon (Salmo salar, L.) - Kalananthan, Tharmini; Murashita, Koji; Rønnestad, Ivar; Ishigaki, Mitsumasa; Takahashi, Kota; Silva, Marta S.; Wakabayashi, Yuki; Lai, Floriana; Shimizu, Munetaka; Nilsen, Tom O.; Pino Martinez, Enrique; Gomes, Ana S. (Frontiers in Physiology, 2020)
The orexigenic agouti-related protein (AgRP) and the anorexigenic pro-opiomelanocortin (POMC) are crucial players in the control of feed intake in vertebrates, yet their role in teleosts has not been fully established. Triplicate groups of Atlantic salmon (Salmo salar) post smolts were subjected to a) fasting for 3 days (fast), and b) normal feeding (fed), resulting in a significant (p < 0.05) upregulation of hypothalamic agrp1 transcripts levels in the fast group. Moreover, the mRNA abundance of agrp1 was significantly (p < 0.05) correlated with the stomach dry weight content. Corresponding inverse patterns were observed for pomca2, albeit not statistically significant. No significant differences were found for the other paralogues, agrp2 and pomca1 and b, between fed and fast groups. The significant correlation between stomach fullness and agrp1 mRNA expression suggests a possible link between the stomach filling/distension and satiety signals. Our study indicates that hypothalamic agrp1 acts as an orexigenic signal in Atlantic salmon.